Pengaruh Edukasi Terintegrasi Terhadap Gangguan Mineral Dan Tulang Pada Penyakit Ginjal Kronik Di Rumah Sakit Dr. Soedjono Magelang - Endro Haksara; Ainnur Rahmanti; Seftian Hidayati; Indra Bayu Woro (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
This study aims to evaluate the positive influence of Integrated Education on body mineral balance and bone health in sufferers of Chronic Kidney Disease (CKD). An experimental research design with a control group was used. The research subjects involved sufferers of stage 3-4 CKD, who were divided into an intervention group (receiving Integrated Education) and a control group (no intervention). Research parameters include levels of calcium, phosphorus, parathormone, bone mineral density, as well as patient knowledge and behavior. Findings: Increased Knowledge: The intervention group experienced a significant increase in knowledge related to CKD management compared to the control group, Positive Behavioral Changes: Patients who took part in the integrated education program showed more positive behavioral changes, including medication adherence, a healthy diet, and a healthy lifestyle, Improvement in Mineral and Bone Disorder Parameters: The intervention group showed significant improvement in calcium, phosphorus and parathormone levels. Bone mineral density also increased significantly. Clinical Implications: The results of the study suggest that Integrated Education can be an effective approach in improving CKD management, with a positive impact on the body's mineral balance and bone health. Conclusion: Integrated education has a significant influence on knowledge, behavior and mineral and bone balance parameters in CKD sufferers. Implementation of this program can improve CKD management and prevent complications related to mineral and bone disorders. Recommendation: Further research could explore the long-term effects of Integrated Education, consider variations in individual responses, and involve a wider sample group.